2007
DOI: 10.1016/j.bmc.2006.09.063
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor studies. Part 1: Design, synthesis, antitumor activity, and AutoDock study of 2-deoxo-2-phenyl-5-deazaflavins and 2-deoxo-2-phenylflavin-5-oxides as a new class of antitumor agents

Abstract: Abstract--Novel 2-deoxo-2-phenyl-5-deazaflavins and 2-deoxo-2-phenylflavin-5-oxides were prepared as a new class of antitumor agents and showed significant antitumor activities against NCI-H 460, HCT 116, A 431, CCRF-HSB-2, and KB cell lines. In vivo investigation, 2-deoxo-10-methyl-2-phenyl-5-deazaflavin exhibited the effective antitumor activity against A 431 human adenocarcinoma cells transplanted subcutaneously into nude mouse. Furthermore, AutoDock study has been done by binding of the flavin analogs into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 14 publications
0
13
0
3
Order By: Relevance
“…Molecular docking studies for binding to protein tyrosine kinase (PTK) showed low binding free energies (Δ G ) and K i values for several compounds, especially for 2‐deoxo‐2‐phenylflavin‐5‐oxides ( 22 ), which displayed Δ G values between −7.84 and −5.95 kcal/mol. The binding free‐energy levels correlated with the IC 50 values obtained against cancer cell lines …”
Section: Antitumor Activitymentioning
confidence: 84%
“…Molecular docking studies for binding to protein tyrosine kinase (PTK) showed low binding free energies (Δ G ) and K i values for several compounds, especially for 2‐deoxo‐2‐phenylflavin‐5‐oxides ( 22 ), which displayed Δ G values between −7.84 and −5.95 kcal/mol. The binding free‐energy levels correlated with the IC 50 values obtained against cancer cell lines …”
Section: Antitumor Activitymentioning
confidence: 84%
“…We investigated the AutoDock binding affinities of various structures for their potential protein tyrosine inhibitory activities, including: 2, 3, 4- trisubstitutred -1, 2-dihydropyrrolo[ 1,2-a ] [ 1, 3, 5 ]triazin derivatives Ia-k, 4-(3, 5-di-tert-butylphenylcarbamoyl)-2-amino benzoic acid, its 2-nitro benzoic acid, their methylester analogs IIa-d such as benzopyrido, benzopyrimido, benzopiprazino [1,4] dioxin-2-ol IIIa-c, dipyrido [1,4] dioxin-2-ol analogs IIId-g, 2-substituted-(6-fluoro-3,4-dihydro-4- substituted pheno-xypyrido [3,4-d] pyrimidin-2-yl) derivatives IVa-d, tyrosine containing di- or tripeptides Va-f, acetylated tyrosine containing tetrapeptides analogs Vg-m, deazapteridine-steroid hybrid compounds VIad, hybrid compounds possessing 5-deazapteridine and steroid in the same ring system [12], 2-deoxo-2-phenyl-5-deazaflavins VIIa-h [13, 14], 2-deoxo-2-piperidino-5-deazaflavin VIIi [15], 2-deoxo-2-morpholino-5- deazaflavin VIIj [15], 2-deoxo-2-phenylflavins VIIm-o, computationally newly designed 2-deoxo-2-glycino, 2-tyrosino, 2-histidino-N10- methylflavin-N-oxides VIIp-r, 5-deazaflavin derivatives VIIIa-c, N3- methyl-5-(monosubstituted alkylamino)-5-deazaflavin derivatives VIIId-g [14], computationally designed pyridodipyrimidines IXa-f [14], and bis- (5-deazaflavin-10-yl) alkanes Xa,b [14]. Additional structures obtained from Sumisho Data Base were studied, including abacavir, PB-01547328, PB-99211665, F0007-0958, OSSK-633719, OSSK-692604, 831, PB- 00623451, and compound 1505335.…”
Section: Resultsmentioning
confidence: 99%
“…The selective PKC inhibitory activities of 5-deazaflavins, 2-deoxy-2- phenyl-5-deazaflavins, {2-phenylpyrimido[4, 5-b]quinolin-4(10H)-ones}, and their effective growth inhibition against cancer cells such as the A431 cells, and HT1080 cells were reported [11]. Synthesis of the hybrid compounds, which structurally contain two different biologically or pharmacologically active compounds of 5-deazaflavins and steroids in the same ring system, were carried out by condensation of 6-(monosubstituted amino)uracils or 6-(monosubstituted amino)-2-phenylpyrimidin-4(3H)- ones with 2-hydroxy-methylene androstanolone or 2- hydroxymethylenetestosterone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the formation of more and/or tighter hydrogen bonds provides higher binding affinities. 22,23 The pyrimidone derivatives 7a,b and 8a-c were deeply embedded into CDK2 binding site displayed ∆G b between -8.31 and -10.81 kcal/mol. Compounds 7a,b and 8c bound to the active site of CDK2 through 2 hydrogen bonds with Leu 83, whereas compound 8b showed 2 hydrogen bonds with Asp145 and Asn132.…”
Section: Docking Studymentioning
confidence: 99%